Peningkatkan Kemampuan Membaca Pemahaman dengan Menggunakan Strategi SQ3R pada Siswa Kelas V SD Inpres BTN IKIP I Kota Makassar - Farida Indriani (Cokroaminoto Journal of Primary Education, 2018)
This study aims to find out how the process of using the SQ3R strategy and whether the implementation of the SQ3R strategy can improve students' reading comprehension skills. This research uses descriptive qualitative approach with the type of research is classroom action research. The population of this study were all fifth grade students of SD Inpres BTN IKIP I Makassar City. Data collection techniques are carried out by means of observation, tests and documentation. The data analysis technique used in this study is descriptive data analysis. Based on the results of the formative tests conducted at the end of the first cycle only reached 66.66% with an average of 7.16 being in sufficient qualifications. During this formative test, only 20 students were able to answer the questions well. In the second cycle increased to 90% or 27 students obtained a score of ≥ 70 with an average of 8.03. Based on observations of student activities, obtained data that student activity experienced a significant increase from cycle I to cycle II. Where in the first cycle, the activities of students have been in the good category and the silus II is in the very good category. Improving student outcomes in reading comprehension shows that the application of SQ3R strategies can improve students' reading comprehension skills.